1969
DOI: 10.1677/joe.0.0440285
|View full text |Cite
|
Sign up to set email alerts
|

Foetal Plasma Corticosteroids and the Initiation of Parturition in Sheep

Abstract: Prolonged pregnancy following foetal hypophysectomy or adrenalectomy (Liggins, Kennedy & Holm, 1967;Drost & Holm, 1968) and premature parturition following injection of corticotrophin or corticosteroids into the ovine foetus (Van Rensburg, 1967;Halliday & Buttle, 1968;Liggins, 1968) implicate the foetal adrenal cortex in the initiation of parturition in sheep. Consequently, foetal plasma corticosteroid concentrations and corticosteroid secretion by the foetal adrenal should be greatly increased towards term. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
91
0

Year Published

1974
1974
2003
2003

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 283 publications
(104 citation statements)
references
References 3 publications
13
91
0
Order By: Relevance
“…In addition, we have demonstrated that the same ACTH infusion regimen in intact fetuses is not sufficient to significantly advance parturition or adrenal maturation. Labour in all groups of fetuses in this study was characterised by an increase in plasma cortisol concentrations beginning around 14 days before term, as shown previously (Bassett & Thorburn 1969, Jacobs et al 1994, but this was not associated with an increase in plasma ir-ACTH concentrations in ACTH (1-24) -infused HX fetuses. This observation was confirmed by assaying ir-ACTH concentrations in two distinct RIAs, thus reinforcing the biological conclusions which may be drawn from the data.…”
Section: Discussionsupporting
confidence: 79%
“…In addition, we have demonstrated that the same ACTH infusion regimen in intact fetuses is not sufficient to significantly advance parturition or adrenal maturation. Labour in all groups of fetuses in this study was characterised by an increase in plasma cortisol concentrations beginning around 14 days before term, as shown previously (Bassett & Thorburn 1969, Jacobs et al 1994, but this was not associated with an increase in plasma ir-ACTH concentrations in ACTH (1-24) -infused HX fetuses. This observation was confirmed by assaying ir-ACTH concentrations in two distinct RIAs, thus reinforcing the biological conclusions which may be drawn from the data.…”
Section: Discussionsupporting
confidence: 79%
“…It is well established that parturition in the sheep is dependent on activation of the fetal hypothalamicpituitary-adrenal axis during late gestation and a concurrent increase in fetal plasma cortisol concentrations (Bassett & Thorburn 1969, Liggins 1976, Thorburn & Challis 1979. There is also an increase in production of oestradiol (E 2 ) from the placenta that follows the increase in circulating glucocorticoid concentrations (Challis & Brooks 1989).…”
Section: Introductionmentioning
confidence: 99%
“…Other methods. -DNA, proteins, ACTH receptors and plasma corticosteroids were assayed as described elsewhere (Durand et al, 1978 ;Durand, 1979 (Rees et al, 1975 ;Challis et al,1977a ;Jones et al,1977a) and confirm that ACTH levels rise only in the very last days of gestation, when cortisol levels are already elevated (Bassett and Thorburn, 1969 ;Liggins et al, 1973 Liggins (19b9), whereas large doses of ACTH anticipated the increase in adrenal weight (Liggins,1968). Figure 2 shows that the infusion of 0.1 mg/24 h of ACTH into the sheep fetus between days 115 and 120 resulted in a 4-fold d increment in adrenal membrane protein content and a 2-fold increase in DNA concentrations.…”
mentioning
confidence: 99%